2. Using Of Natural Spaces For Tourism Activity Scuba Diving And Impacts On Aquatic Animals - Luis Mota (The International Journal of Tropical Veterinary and Biomedical Research, 2016)
There were few previsions to strongly expand the growth of scuba diving activity, and nowadays training standards are enforced for safety and also for respecting the natural space where dive tourism takes place. Based on literature review, environmental impacts were noted in terms of providing positive aspects, mainly represented by economic benefits and employment opportunities. The negative side was revealed by wildlife impacts whereby animals change their behavior due harassment or contact with nature-based users, with authors reporting their concerns and measuring the consequences and long-term learning impacts. The over-usage of the reefs can result in physical devastation and chemical contamination. Land development in support of scuba diving can also cause negative impacts and affect the surrounding infrastructure, with alternating living patterns and by creating economic differences among the local society. When dive techniques are mastered, scuba diving itself does not represent a threat to the environment, neither to marine animals, but bad dive practices, poor buoyancy control associated to the lack of awareness can contribute to damage the benthic zone. Divers physical impact on the reef can benefit some species looking for opportunity to feed or compete for space, although, it destroys the habitat and lifting up sediment affect negatively coral structures by inducing stress and reducing the average amount of light.